Информация в природных кибернетических системах (к определению термина информация) - Решетник, В.Я. (Проблемы управления и информатики, 2020)
Розглянуто модель атмосфери як природної кібернетичної системи з керуванням за принципом Больцмана і показано, що інформацією в природних системах є зростання ентропії при порушенні балансу енергії. Виконано аналіз визначення інформації Шеннона і сформульовано об’єктивне визначення інформації, яке за всіма ознаками співпадає з визначенням Шеннона. The model of natural cyber system, realising the control of the atmosphere state according to the Boltsman principle, has been analised. It was shown that the information in the natural systems is that of entropy raising under the energy balanse break. The analysis of the Shannon information statement was performed and the single objective determination of information was stated due to all features according to the Shannon statement.